The Effects of Rain Fade on Millimetre Wave Channel in Tropical Climate - Ali Budalal, Asma; Md Rafiqul, Islam; Hadi Habaebi, Mohamed; Abd. Rahman, Tharek (Institute of Advanced Engineering and Science, 2019)
Abstract—The main objective of this paper to determine multipath and time varying channel behavior of short- terrestrial millimetre-wave point-to-point radio links. With considering of rain fade in tropical climate. In an attempt to invigorate the impact of rain attenuation on mm-wave channel parameters such as the RMS delay spread, path loss received power strength and Rician distribution with a K factor. A brief analysis of rain fading was presented based on the simultaneous measurement of one-minute rain rate and its effects on a short experimental link of 38 GHz. Rain fade average is observed as high as 16 dB for 300 m path at about 125 mm/hr rain intensity. The statistical spatial channel mode (SSCM)simulation software was utilized for an operating frequency of 38 GHz. To generate of power delay profile (PDP). For both omnidirectional and directional antenna. The RMS delay spread, path loss has been estimated using the environmental parameters of Kuala Lumpur city which illustrates the theoretical performances of 5G in Malaysia. it is observed that RMS delay spread, path loss received power strength and K factor effected dramatically by rein fade. (SSCM) simulation software has to be modified to consider rain fade dynamic in the tropical area. This study is important for understanding signal propagation phenomena in short distance and enabling the utilization of the millimeter wave band in outdoor activities for 5 G communication system in outdoor in tropical regions.